Compartimentação e evolução geomorfolófica da borda ocidental da Serra da Canastra - MG - Cortes, João Paulo Soares de [UNESP] (2014)
The influence of structural factors on relief formation has been investigated since long time on geomorphology. On the other hand, the discussion involving different uplift and generalized planation events on the Brazilian platform has been intensified as soon as new data and techniques contribute to establish an integrative view of such events. The occidental border of Serra da Canastra is a key area to investigate these processes, once it contains different morphotectonic domains. In this work is proposed a regional geomorphological and structural compartmentation, in a way to better understand the role of the lithological and structural background on its relief evolution. To achieve this, we use geomorphological, geological and geophysical data collected on field and extracted from remote sensing products, integrated in a GIS environment. The use of such data allowed to propose a geomorphological compartmentation, a better detailed geological mapping and an evolutionary model for the relief since the Jurassic/Cretaceous transition, contributing for the discussion involving the main identified morphotectonic events and its influence on the recent landscape configuration